PEREMPUAN BEKERJA (TINJAUAN GENDER EQUALITY DALAM PERAN KELUARGA) - Ahmad Zayyadi (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2012)
Abstract: In the recent time, the reality of our society is still under a patriarchal system which causes such cases as marginalization, subordination, stereotype, and even violence. The subtle gender difference quickly spread through the society urges women to act according to the competence they have. However, behind this paradigm and any negative stereotype of women lie their superiority and excellence more than those of men. We see, in this modern time, women serve in more public fieldwork than men do, thereby making us know terms like a career or working woman and what Karl Marx called as double burden. This work tends to offer a paradigm of gender equality, in the sense that all human being has the same right equally in getting jobs in varied fieldwork by means of setting aside any of those superficial differences. They have to get jobs with respect professionally to each competence instead of gender-based recruitment. Kata Kunci: perempuan bekerja, kesetaraan gender, dan keluarga.